Uji Toksisitas Akut Air Limbah Industri Sasirangan Terhadap Ikan Nila (Oreochromis Niloticus) - Akhmad Yafi Kusuma; Rahmawati Rahmawati; Hardiono Hardiono (JURNAL KESEHATAN LINGKUNGAN: Jurnal dan Aplikasi Teknik Kesehatan Lingkungan, 2019)
Abstract: Toxicity Test Of Acute Industrial Waste Water On Tilapia Fish (Oreochromis Niloticus). The sasirangan industrial liquid wastes containing high ammonia and high pH when discharged into the receiving water body without treatment will result in changes in water quality and even the death of aquatic biota so that an acute toxicity test is necessary. This study aims to determine the value of LC50 from waste sasirangan against tilapiaI. This research used the experimental method of Post Control Only Control Group Design design. Samples taken as much as 100 liters of waste in one industry sasirangan existing in the city of Banjarmasin. Concentrations of the sasirangan waste solution to be used in the acute toxicity test are: 4, 8, 12, 16 and 20%. Parameters studied include ammonia, DO, pH, and temperature. To determine the value of LC50 using probit analysis. The results showed that LC50 for exposure time 24, 48, 72 and 96 hours were 14.73%, 10.21%, 8.26%, and 7.35%, respectively. The results of the analysis show that pH and ammonia content of industrial effluent sasirangan affect the death of tilapia fish. This research is hoped that the sasirangan industry does not dispose of its waste directly to the water body but needs to process it first. For further research it can complement the untested parameters such as BOD, COD, and TSS that affect fish survival.